Analysis of Outpatient Waiting Time Determinants in Hospitals Based on the Donabedian Framework - Rika Maretha; Haerawati Idris; Rizma Adlia Syakurah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Waiting time is one of the indicators in evaluating the quality of outpatient services in hospitals. Long waiting times are often the main complaint of patients and have the potential to reduce satisfaction and effectiveness of services. This article aims to review the available literature on patient waiting times and identify factors that contribute to waiting times for outpatient services. The method used is a Systematic Literature Review using the Preferred Reporting Items for Systematic Reviews (PRISMA) flow by collecting articles from the Google Scholar and PubMed databases published between 2019 and 2024 with the keywords